Sunlight driven photoelectrochemical light-to-electricity conversion of screen-printed surface nanostructured TiO2 decorated with plasmonic Au nanoparticles. (20th November 2016) - Siavash Moakhar, Roozbeh; Masudy-Panah, Saeid; Jalali, Mahsa; Goh, Gregory Kia Liang; Dolati, Abolghasem; Ghorbani, Mohammad; Riahi-Noori, Nastaran
Graphical abstract: Highlights: TiO2 porous nanorods (PNR-TiO2 ) photoelectrode was fabricated via screen-print method. Photoelectrochemical light-to-electricity was developed based on Au nanoparticle decoration of PNR-TiO2 photoelectrode (Au-PNR-TiO2 ). Au-PNR-TiO2 photoelectrode exhibited photocurrent density of 0.71 and 0.07 mA cm −2 under sunlight and visible light radiation, respectively. PNR-TiO2 nanorods make a great microenvironment for more accessible reactive sites, light capturing ability and efficient charge generation. Au enhanced PEC performance due to SPR-mediated hot electron injection, catalytic effect and well-stablished schottky barriers. Abstract: In this paper, we report a promising sunlight-driven screen-printed TiO2 porous nanorods (PNR) photoanode decorated with Au plasmonic nanostructures for photoelectrochemical (PEC) light-to-electricity conversion. Fabricated photoanodes were characterized using field emission scanning electron microscopy, high-resolution transmission electron microscopy, energy dispersive spectroscopy, X-Ray diffraction analysis, X-ray photoelectron spectroscopy, N2 adsorption-desorption isotherms, UV–vis spectroscopy and electrochemical impedance spectroscopy in detail. The Au-PNR-TiO2 photoanode demonstrates superior PEC activities both under simulated sunlight and visible light irradiation. Interestingly, the Au-PNR-TiO2 shows high photocurrent density of 0.71 mA cm −2 at +0.4 V vs. Ag/AgCl, which is 65% higher than the pristine PNR-TiO2 . It is shown that enhanced surface area, roughness factor, high crystallinity and one-dimensional framework which are offered by screen-printed porous TiO2 nanorods make a great microenvironment for more accessible reactive sites, light capturing ability, efficient charge generation and smooth transfer of photogenerated charge carriers. Decoration with Au nanoparticles is also shown that play an important role in improving the PEC performance by injecting hot electrons and excellent catalytic effect.